Wandering stars ebook A novel. - Orange, Tommy (2024)
NEW YORK TIMES BESTSELLER • LONGLISTED FOR THE BOOKER PRIZE • A NEW YORK TIMES NOTABLE BOOK • A TIME MUST-READ BOOK OF THE YEAR • The Pulitzer Prize-finalist and author of the breakout bestseller There There ("Pure soaring beauty." The New York Times Book Review) delivers a masterful follow-up to his already classic first novel. Extending his constellation of narratives into the past and future, Tommy Orange traces the legacies of the Sand Creek Massacre of 1864 and the Carlisle Indian Industrial School through three generations of a family in a story that is by turns shattering and wondrous. "For the sake of knowing, of understanding, Wandering Stars blew my heart into a thousand pieces and put it all back together again. This is a masterwork that will not be forgotten, a masterwork that will forever be part of you.” —Morgan Talty, bestselling author of Night of the Living Rez Colorado, 1864. Star, a young survivor of the Sand Creek Massacre, is brought to the Fort Marion prison castle, where he is forced to learn English and practice Christianity by Richard Henry Pratt, an evangelical prison guard who will go on to found the Carlisle Indian Industrial School, an institution dedicated to the eradication of Native history, culture, and identity. A generation later, Star’s son, Charles, is sent to the school, where he is brutalized by the man who was once his father’s jailer. Under Pratt’s harsh treatment, Charles clings to moments he shares with a young fellow student, Opal Viola, as the two envision a future away from the institutional violence that follows their bloodlines. In a novel that is by turns shattering and wondrous, Tommy Orange has conjured the ancestors of the family readers first fell in love with in There There —warriors, drunks, outlaws, addicts—asking what it means to be the children and grandchildren of massacre. Wandering Stars is a novel about epigenetic and generational trauma that has the force and vision of a modern epic, an exceptionally powerful new book from one of the most exciting writers at work today and soaring confirmation of Tommy Orange’s monumental gifts.